Implementasi Standar Nasional Perpustakaan (SNP 008:2017) pada Standar Koleksi dan Sarana Prasarana di Dinas Perpustakaan dan Kearsipan Kota Padang - Zurini, Fitri; Erlianti, Gustina (ARZUSIN, 2024)
The purpose of this study is to describe how the implementation of national library standards on collection standards and infrastructure facilities at the Padang City Library and Archives Service based on the National Library Standards (SNP 008:2017). The method used in the research is the descriptive method, with a qualitative type of research. The background of the research was carried out at the Padang City Library and Archives Office located in Gor Haji Agus Salim Padang. Data entry to be done obtained from interviews and documentation that the author will do directly at the Padang City Library and Archives Office. The selection of informants was carried out by purposive sampling techniques Data collection techniques used interviews, and documentation. The results of this study show that (1) the collection standard that has not met the standard is the type of library collection because for the type of collection in the form of Electronics and recorded works do not exist yet, for the number of library collections is sufficient However, for the procurement of collections has not been carried out in accordance with the national library standards because they are constrained by the budget, the up-to-date collections have also not met the standards because there are still many collections published in the old year, the development of collections has not been in accordance with standards because there have never been re-shuffling activities, the procurement of library materials has not been carried out according to standards because they are constrained by The budget, the up-to-date collection has also not met the standards because many collections published in the old year are still used, the development of collections has not been in accordance with standards because there have never been re-opening activities, the procurement of library materials has not been carried out according to standards because of budget constraints, the preservation of collections has not been in accordance with standards because there are no tools that can be used for collection preservation, and the processing of library materials has been carried out in accordance with standards national libraries.